P14.66 Re-operation for recurrent meningioma - are we helping patients?. (9th September 2021) - Richardson, G E; Mustafa, M A; Gillespie, C S; Keshwara, S M; Taweel, B A; Millward, C P; Islim, A I; Jenkinson, M D
Abstract: BACKGROUND: Meningioma is the commonest primary brain tumour. Despite surgery, meningiomas can recur. Surgery is usually the first line treatment for recurrent meningioma. The aim was to determine the risk factors associated with clinical outcomes (performance status, morbidity, mortality, recurrence) following re-operation for recurrence of intracranial meningioma. MATERIAL AND METHODS: Retrospective cohort study (1998–2018). Eligible patients had reoperation for local recurrence of a previously operated meningioma. Collected data included baseline clinical and imaging characteristic. Primary outcome measure was performance status after each reoperation. Secondary outcome measures were medical and surgical morbidity, recurrence-free survival (RFS) and overall survival (OS). RESULTS: Fifty-eight patients were eligible (37 female, mean age at 1st re-operation 56.1 years (SD=11.6)). Eleven patients (19.6%) had 2 re-operations and 3 patients (5.4%) had 3 re-operations. Median follow up was 128.5 months (IQR=73–194.5). Median time to 1st recurrence and 1st re-operation were 36.5 (IQR=24.3–81.0) and 43.8 months (IQR=20.3–103.4), respectively. Fifteen patients (26.8%) had worse performance status after 1st reoperation, compared to 5.4% (n=3) after the primary operation. Complication rate was 32.1% (n=18) after the primary operation compared to 48.2% (n=27) after 1st reoperation. At primary operation, there were 29 (51.8%) grade 1, 24 (42.9%) grade 2, and 1 (1.8%) grade 3 tumours. Median RFS after first re-operation was 36.5 months (95% CI 29.3–43.9). Median OS was 312 months (95 % CI 257.8–366.2). Increased number of post-operative complications were a risk factor for worsened performance status following reoperation (OR 2.2 [95% CI 1.1–4.6], P=0.029). CONCLUSION: Re-operation is associated with a worse performance status and increased risk of complications. Re-operating meningiomas for radiological recurrence without symptoms increases patient morbidity. Shared-care management decision should be made with patients when considering operating for radiological recurrence only.